Hungry for more: key stakeholders' support for more stringent school food policies - Pettigrew, Simone; Talati, Z.; Sauzier, M.; Ferguson, A. (Cambridge University Press, 2019)
Objective: School food policies are an important component of comprehensive strategies to address child obesity and improve children's health. Evaluations have demonstrated that these policies can be initially well accepted and appropriately implemented, however little is known about how acceptance levels may change over time. The present study aimed to re-evaluate a school food policy 10 years after its introduction to assess key stakeholders' support for various policy extensions that would strengthen the scope of the policy. DESIGN: Online surveys administered 1 year after policy introduction (n 607, 2008) and 10 years after policy introduction (n 307, 2016). Setting: Western Australia.ParticipantsSchool principals, teachers, canteen managers and presidents of parents & citizens associations from Western Australian Government primary schools. Results: At both time points, and especially at time 2 (10 years post policy implementation), high levels of support were reported for the policy and possible policy extensions. Support was strongest for an additional requirement to integrate the canteen menu with the classroom health curriculum. Conclusions: The results suggest that once a policy has become embedded into school practices, stakeholders may be receptive to modifications that strengthen the policy to enhance its potential effects on children's diets.